Manufacturing method of welded joint and flux-cored cut wire for filling groove

By employing flux-containing cut wires with high-alloy elements, the inefficiencies in welding low-temperature steels are addressed, resulting in high-efficiency welding joints with enhanced mechanical properties.

JP7623566B2Active Publication Date: 2025-01-29NIPPON STEEL CORPORATION
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020170006
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-07
Publication Date
2025-01-29
Estimated Expiration
2040-10-07

AI Technical Summary

Technical Problem

Existing welding methods for low-temperature steels, such as 5.5%NI steel and 6-7%NI steel, face inefficiencies due to the limitations of conventional filler materials, particularly in submerged arc welding, which do not adequately utilize high-alloy wires to enhance construction efficiency.

Method used

The use of flux-containing cut wires filled with high-alloy elements like Ni, Cr, Mo, and W, along with controlled chemical components and impurities, to ensure high tensile strength and toughness in weld metals, particularly for low-temperature steels.

Benefits of technology

This approach enables high-efficiency welding joints with improved mechanical characteristics, ensuring tensile strength and toughness even at low temperatures, thereby enhancing construction efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623566000005
    Figure 0007623566000005
  • Figure 0007623566000006
    Figure 0007623566000006
  • Figure 0007623566000007
    Figure 0007623566000007
Patent Text Reader

Abstract

To provide a method for manufacturing a weld joint which enables welding with higher efficiency than a conventional method by SAW welding even when a base material is steel for low temperature, and has high weld efficiency, and a flux-cored cut wire used in the same.SOLUTION: There are provided a method for filling the inside of a groove with a flux-cored cut wire having a steel sheath and a flux that is made to fill the inside of the steel sheath, and welding the groove, in which the flux contains a high alloy element (Ni, Cr, Mo and W), and a content of Ni is 50 mass% or more of the total content of the high alloy element; and a flux-cored cut wire used in the same.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a welded joint in which a cut wire is filled into a groove provided between base materials and welded, and to a flux-cored cut wire for filling the groove used in the method. [Background technology]

[0002] In view of recent global environmental problems, the demand for liquefied natural gas (hereinafter abbreviated as "LNG") as clean energy is increasing. Ferritic cryogenic materials, such as 5.5% Ni steel, 6-7% Ni steel, 9% Ni steel, etc. (hereinafter referred to as "low-temperature steel") have been used as the inner tank material of LNG storage tanks. The welds of these low-temperature steels require low-temperature toughness as welded (i.e., the welds after welding are not subjected to material changes such as heat treatment and peening), so Ni-based alloy wires with a higher Ni content than the base material are used. In on-site construction, submerged arc welding (SAW) methods, shielded arc welding, TIG welding methods, etc. are applied. However, shielded arc welding and TIG welding have a problem of poor construction efficiency.

[0003] As a technique for solving this problem, Patent Documents 1 and 2 disclose SAW welding materials suitable for low-temperature steels. Patent Document 1 proposes using a Ni-based alloy welding wire with a Ni content of 65.0 to 82.4 mass%, and Patent Document 2 proposes performing SAW welding of 9% Ni steel using a wire with a Ni content of 60 mass% or more and a sintered flux containing 15 to 40 mass% Al2O3, 5 to 35 mass% SiO2, 5 to 25 mass% ZrO2, 5 to 25 mass% MgO, 5 to 25 mass% CaCO3, and 1 to 7 mass% metallic Al. However, in order to further improve the efficiency of SAW welding, the use of a Ni-based alloy welding wire as disclosed in Patent Document 1 or the combined use of a wire having a Ni content of 60 mass % or more and a sintered flux as disclosed in Patent Document 2 was insufficient because it was not possible to ensure a high deposition rate. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6,418,365 [Patent Document 2] JP 2011-025285 A Summary of the Invention [Problem to be solved by the invention]

[0005] In order to achieve high efficiency welding of low temperature steel, it is desirable to fill the groove with cut wire and perform welding. However, there has been no filler material containing high alloy suitable for welding low temperature steel. This is because the conventional filler material is a cut wire made of solid wire, and the composition of the filler material is limited to a composition that can be drawn.

[0006] Therefore, the inventors conducted intensive research to solve this problem, and discovered that the above problem can be solved by filling the groove with a cut wire cored with flux containing a specified element and welding it, and thus completed the present invention. That is, the inventors solved the above problem by using a steel sheath capable of wire drawing and a flux-cored cut wire filled inside the steel sheath, and by making the flux-cored cut wire contain a predetermined highly alloying element capable of highly alloying. In addition, the inventors found that the occurrence of hot cracking, which is a problem in high alloys, can be suppressed by adding a predetermined strong deoxidizing element to the flux.

[0007] Therefore, an object of the present invention is to provide a method for manufacturing a welded joint with high welding efficiency, which can use a flux-cored cut wire to perform welding more efficiently than ever before by SAW welding, even if the base material is low-temperature steel. Another object of the present invention is to provide a flux-cored cut wire for use in the method for producing such a welded joint. [Means for solving the problem]

[0008] That is, the gist of the present invention is as follows. (1) A method for manufacturing a welded joint in which a cut wire is filled into a groove provided between base materials and welded by submerged arc welding, A welding method in which a flux-cored cut wire having a steel sheath and flux filled inside the steel sheath is filled into the groove, A method for manufacturing a welded joint, characterized in that the flux contains one or more highly alloying elements selected from the group consisting of Ni, Cr, Mo, and W as a metal and / or alloy, and the Ni content is 50 mass% or more of the total content of the highly alloying elements. (2) The flux-cored cut wire has a mass ratio to the total mass of the flux-cored cut wire of: The total content of the high alloying elements is 50% or more and 98% or less, the contents of the chemical components consisting of C, Si, Mn, Cu, Nb, V, Al, B, and Bi are C: 0.120% or less, Si: 2.00% or less, Mn: 3.50% or less, Cu: 5.00% or less, Nb: 0.50% or less, V: 0.500% or less, Al: 1.70% or less, B: 0.020% or less, and Bi: 0.030% or less, and the content of one or more strong deoxidizing elements selected from the group consisting of Ca, Mg, Ti, Zr, and REM is 4.0% or less in total, and The method for producing a welded joint according to (1) above, characterized in that the contents of impurity elements consisting of P and S are P: 0.030% or less and S: 0.020% or less. (3) The method for manufacturing a welded joint according to (2) above, characterized in that the strong deoxidizing element is contained in the flux-cored cut wire as an oxide and / or an alloy, and the total content thereof is 0.005% or more and 4.0% or less by mass relative to the total mass of the flux-cored cut wire.

[0009] (4) A cut wire for groove filling, which is used to fill a groove between base materials to produce a welded joint, A steel sheath and a flux filled inside the steel sheath, A flux-cored cut wire for groove filling, characterized in that the flux contains one or more highly alloyed elements selected from the group consisting of Ni, Cr, Mo, and W as a metal and / or alloy, and the Ni content is 50 mass% or more of the total content of the highly alloyed additive elements. (5) The mass ratio of the flux-cored cut wire to the total mass of the flux-cored cut wire is The total content of the high alloying elements is 50% or more and 98% or less, the contents of the chemical components consisting of C, Si, Mn, Cu, Nb, V, Al, B, and Bi are C: 0.120% or less, Si: 2.00% or less, Mn: 3.50% or less, Cu: 5.00% or less, Nb: 0.50% or less, V: 0.500% or less, Al: 1.70% or less, B: 0.020% or less, and Bi: 0.030% or less, and the content of one or more strong deoxidizing elements selected from the group consisting of Ca, Mg, Ti, Zr, and REM is 4.0% or less in total, and The flux-cored cut wire for groove filling according to (4) above, characterized in that the contents of impurity elements consisting of P and S are P: 0.030% or less and S: 0.020% or less. (6) The flux-cored cut wire for groove filling according to (5) above, characterized in that the strong deoxidizing element is contained in the flux-cored cut wire as an oxide and / or an alloy, and the total content thereof is 0.005% or more and 4.0% or less by mass relative to the total mass of the flux-cored cut wire. (7) The flux-cored cut wire for groove filling according to any one of (4) to (6) above, which is used by filling a groove provided between base materials. Effect of the Invention

[0010] According to the present invention, for example, even when low-temperature steel is welded by manual SAW welding, hot cracking can be prevented and a welded joint can be manufactured with advantageous construction efficiency. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is an explanatory diagram showing an example of a flux-cored cut wire welding process according to the present invention. [Diagram 2] FIG. 2 is an explanatory view showing another example of the flux-cored cut wire welding process according to the present invention. [Diagram 3] FIG. 3 is an explanatory diagram showing the groove shape used in the tensile test and the impact test in the examples and the state in which the flux-cored cut wire is filled into the groove. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention uses a flux-cored cut wire having a steel outer skin and flux filled inside the steel outer skin, and includes a flux-cored cut wire welding process in which the flux-cored cut wire is filled into a groove provided between base materials and welded, thereby manufacturing a welded joint. Hereinafter, the flux-cored cut wire according to the present invention will be described, along with a method for manufacturing a welded joint using the same.

[0013] [Flux-cored cut wire] First, for the flux-cored cut wire, the flux used contains one or more highly alloying elements selected from the group consisting of Ni, Cr, Mo, and W, and the Ni content is 50 mass % or more of the total content of the highly alloying elements. These highly alloying elements have a significant effect of making the structure of the weld metal an austenitic structure and ensuring the tensile strength and toughness of the weld metal at low temperatures (e.g., −196° C.).

[0014] As described above, the high alloying elements (Ni, Cr, Mo, and W) of the present invention must be contained in a predetermined amount from the viewpoint of ensuring the mechanical properties in the weld metal. In particular, Ni is an essential element, and its content should be 50 mass% or more of the total content of the high alloying elements, preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more. If the Ni content is less than 50 mass%, it becomes difficult to ensure the tensile strength and toughness of the weld metal.

[0015] In addition, in the high alloying elements of the present invention, the total content of Cr, Mo, and W other than Ni is preferably 5 mass% or more, more preferably 10 mass% or more, and further preferably 20 mass% or more. In other words, as long as the amount of Ni contained in the flux is about 50 mass% or more, the lower limit of the total content of Cr, Mo, and W other than Ni is not particularly limited, and each content may be 0 mass%.

[0016] Here, in the flux-cored cut wire of the present invention, the total content of the highly alloyed elements (Ni, Cr, Mo, and W) is usually 50% or more and 98% or less in mass ratio to the total mass of the flux-cored cut wire. The upper limit of the total content of the highly alloyed elements is not particularly limited, but considering that the inside of the steel sheath is filled with flux, the upper limit is practically 98%, and this upper limit may be 95%, 90%, or even 85%. The lower limit of the total content of the highly alloyed elements is sufficient to exhibit the effects of the present invention as long as it is 50% or more, but 55% is even better, and this lower limit may be 60%, 65%, or 70%.

[0017] In addition, the flux-cored cut wire of the present invention may contain, in addition to the above-mentioned high alloying elements (Ni, Cr, Mo, and W), alloying elements (hereinafter, these chemical components and alloying elements are simply referred to as "chemical components") for controlling the chemical components and carbon equivalent (Ceq) of the weld metal, and further strong deoxidizing elements. Here, the chemical components are alloying elements and melt in the same manner as the steel sheath during welding, so that they may be contained in the flux in the form of, for example, metal powder or alloy powder, may be contained in the form of the steel sheath, or may be contained as plating on the outer surface of the steel sheath, and in any case, the same effect is obtained. Note that, unlike the case of a flux-cored wire that is not a cut wire, these chemical components other than the high alloying elements do not need to be in the form of oxides or carbonates, and may be contained in the form of metal powder or alloy powder as described above, since arc stability and all-position weldability are not required. As for the strong deoxidizing element, for example, one or more of Ca, Mg, Ti, Zr, and REM (rare earth metals) are preferably added to the flux-cored cut wire as oxide and / or alloy, preferably as ferroalloy or oxide. By using them as oxide and / or alloy, the oxide is spherical and the alloy is easily deformed, so that the flux-cored cut wire is less likely to break during production, especially during wire drawing. Here, REM refers to a total of 17 elements, including 15 elements with atomic numbers 57 to 71 and two elements Sc and Y, and any one of them or a mixture of two or more of them can be used. The content of REM is the total content of the 17 elements.

[0018] Specifically, the flux-cored cut wire of the present invention has a mass ratio of: The steel contains the highly alloying elements (Ni, Cr, Mo, and W) in a total ratio of 50% to 98%, and also contains, as optional components, one or more chemical components selected from the group consisting of C, Si, Mn, Cu, Nb, V, Al, B, and Bi, and one or more strong deoxidizing elements selected from the group consisting of Ca, Mg, Ti, Zr, and REM, and the content of each of the chemical components is C:0. 120% or less, Si: 2.00% or less, Mn: 3.50% or less, Cu: 5.00% or less, Nb: 0.50% or less, V: 0.500% or less, Al: 1.70% or less, B: 0.020% or less, and Bi: 0.030% or less, the content of the strong deoxidizing elements is 4.00% or less in total, and the contents of the impurity elements P and S are P: 0.030% or less and S: 0.020% or less, respectively. In the present invention, since the above-mentioned high alloying elements are contained, strength and toughness can be ensured without containing the above-mentioned optional chemical components and strong deoxidizing elements, and therefore the lower limit of each of the contents of these optional chemical components and strong deoxidizing elements is 0%.

[0019] Among these, regarding "C: 0.120% or less" in the chemical components contained as optional components, C is an important element for ensuring the proof stress and tensile strength of the weld metal by solid solution strengthening. However, if the C content in the flux-cored cut wire exceeds 0.120%, the C content in the weld metal becomes excessive, and the proof stress and tensile strength of the weld metal increase excessively, and the toughness of the weld metal decreases. In order to stably ensure all of the toughness, proof stress, and tensile strength of the weld metal, it is preferable to set the upper limit of this C content to 0.10%. On the other hand, the lower limit of the C content is 0%, but if necessary, the lower limit of the C content may be 0.010%, 0.020%, 0.030%, 0.040%, or 0.050%. Similarly, the upper limit of the C content may be 0.100%, 0.090%, 0.080%, or 0.070%.

[0020] Regarding "Si: 2.00% or less", Si is a deoxidizing element and has the function of reducing the amount of oxygen in the weld metal and increasing the cleanliness of the weld metal. If the Si content in the flux-cored cut wire exceeds 2.00%, Si deteriorates the toughness of the weld metal. In order to stably ensure the toughness of the weld metal, the upper limit of the Si content may be 1.90%, 1.80%, 1.70%, or 1.50%. On the other hand, the lower limit of the Si content is 0%, but if necessary, the lower limit of the Si content may be 0.01%, 0.02%, 0.03%, or 0.04%.

[0021] Regarding "Mn: 3.50% or less", Mn is an element necessary for ensuring the hardenability of the weld metal and increasing the strength of the weld metal, but it may be 0%. In order to increase the strength of the weld metal, the lower limit of the Mn content in the flux-cored cut wire may be set to 0.50%, 0.75%, or 1.0%. On the other hand, if the Mn content exceeds 3.50%, the susceptibility of the weld metal to grain boundary embrittlement increases and the toughness of the weld metal deteriorates. Therefore, although the upper limit of the Mn content is 3.50%, the upper limit of the Mn content may be set to 3.00%, 2.50%, or 2.00%.

[0022] Regarding "Cu: 5.00% or less", Cu has the effect of improving the strength and toughness of the weld metal, but it may be 0%. Cu may be contained in the plating on the surface of the steel sheath of the flux-cored cut wire, or may be contained in the flux as a single element or as an alloy. This Cu content is the total amount of Cu contained in the steel sheath or flux and Cu contained in the plating on the surface. If this Cu content exceeds 5.00%, the toughness of the weld metal decreases. The upper limit of the Cu content is preferably 4.00%, 3.00%, or 2.00%. The lower limit of the Cu content is preferably 0.05%, 0.1%, or 0.15%.

[0023] Regarding "Nb: 0.50% or less", since Nb is not an essential component, the lower limit of the Nb content in the flux-cored cut wire is 0%. On the other hand, Nb forms fine carbides in the weld metal, and these fine carbides cause precipitation strengthening in the weld metal, so Nb improves the tensile strength of the weld metal. In order to fully obtain this effect, it is preferable that the Nb content is 0.005% or more. However, it is not preferable for the Nb content to exceed 0.50%, because Nb forms coarse precipitates in the weld metal and deteriorates the toughness of the weld metal. The upper limit of the Nb content is preferably 0.40%, 0.30%, 0.20%, or 0.10%.

[0024] Regarding "V: 0.500% or less", since V is not an essential component, the lower limit of the V content in the flux-cored cut wire is 0%. On the other hand, V improves the hardenability of the weld metal, and is therefore an effective element for increasing the strength of the weld metal. In order to fully obtain this effect, it is preferable that the V content is 0.010% or more. If the V content exceeds 0.500%, the amount of precipitation of V carbides in the weld metal becomes excessive, causing the weld metal to become excessively hard, thereby deteriorating the toughness of the weld metal. The upper limit of the V content is preferably 0.400%, 0.300%, 0.200%, or 0.100%.

[0025] Regarding "Al: 1.70% or less", Al is a deoxidizing element, and like Si, it reduces the amount of oxygen in the weld metal and has the effect of improving the cleanliness of the weld metal. If the Al content in the flux-cored cut wire exceeds 1.70%, Al forms nitrides and oxides, etc., and reduces the toughness of the weld metal. Therefore, the upper limit of the Al content in the flux-cored cut wire is set to 1.70%. This upper limit is preferably 1.60%, 1.50%, 1.40%, or 1.30%. The lower limit of the Al content is preferably 0.005%, 0.010%, 0.050%, 0.100%, 0.150%, or 0.200%.

[0026] Regarding "B: 0.020% or less", since B is not an essential component, the lower limit of the B content in the flux-cored cut wire is 0%. On the other hand, B combines with solute N in the weld metal to form BN, and therefore has the effect of reducing the adverse effect of solute N on the toughness of the weld metal. In addition, B increases the hardenability of the weld metal, and therefore has the effect of improving the strength of the weld metal. For this reason, the flux-cored cut wire may contain 0.0005% or more of B. However, if the B content exceeds 0.020%, the B in the weld metal becomes excessive, and coarse BN and Fe are generated. 23 This is undesirable because it forms B compounds such as (C, B)6 and deteriorates the toughness of the weld metal. The upper limit of the B content is preferably 0.015%, 0.010%, 0.005%, 0.003%, or 0.001%.

[0027] Regarding "Bi: 0.020% or less", since Bi is not an essential component, the lower limit of the Bi content in the flux-cored cut wire is 0%. Meanwhile, Bi is an element that improves the removability of slag. To fully obtain this effect, the Bi content is preferably 0.005% or more, 0.010% or more, or 0.012% or more. Meanwhile, if the Bi content exceeds 0.020%, solidification cracking is likely to occur in the weld metal, so the upper limit of the Bi content is 0.020%. This upper limit of the Bi content is preferably 0.020%, 0.015%, 0.010%, or 0.005%.

[0028] The total content of Ca, Mg, Ti, Zr, and REM contained as strong deoxidizing elements is preferably 4.0% or less, and each of the strong deoxidizing elements is preferably 2.00% or less. Since these strong deoxidizing elements are not essential components, the lower limit of the content of each of these strong deoxidizing elements in the flux-cored cut wire is 0%. However, since each of these strong deoxidizing elements improves hot cracking resistance, it is preferable to add them when hot cracking is a concern, and to fully obtain the effect, it is preferable to set the total content to 0.005% or more, 0.010% or more, or 0.012% or more by mass relative to the total mass of the flux-cored cut wire. On the other hand, if the total content of these strong deoxidizing elements exceeds 4.00%, oxides in the weld metal aggregate and the toughness is likely to deteriorate, so the upper limit is 4.00%, preferably 3.90%, and the upper limit may be 3.80%, 3.7%, 3.6%, 3.5%, or 3.0%.

[0029] Furthermore, since P, present as an impurity element in "P: 0.030% or less", reduces the toughness of the weld metal, it is necessary to reduce the P content in the flux-cored cut wire as much as possible. Therefore, the lower limit of the P content is 0%. Furthermore, if the P content is 0.030% or less, the adverse effect of P on the toughness falls within an allowable range. In order to prevent solidification cracking of the weld metal, the P content is more preferably 0.020% or less, 0.015% or less, or 0.010% or less.

[0030] In the "S: 0.020% or less" content of S present as an impurity element, if excessively present in the weld metal, it deteriorates both the toughness and ductility of the weld metal, so it is desirable to reduce the S content in the flux-cored cut wire as much as possible. Therefore, the lower limit of the S content is 0%. Furthermore, if the S content is 0.020% or less, the adverse effects of S on the toughness and ductility of the weld metal are within an acceptable range. More preferably, it is 0.010% or less, 0.008% or less, 0.006% or less, or 0.005% or less.

[0031] The flux-cored cut wire of the present invention may or may not contain the above-mentioned chemical components and strong deoxidizing elements, but in addition to these chemical components and strong deoxidizing elements, the high alloying elements (Ni, Cr, Mo, and W), and impurity elements, the wire contains Fe and impurities. Among these, Fe may be contained as a steel sheath or as iron powder. That is, in order to adjust the flux filling rate in the flux-cored cut wire or to improve welding efficiency, iron powder may be contained in the flux as necessary. The content of this iron powder is not particularly limited, but since oxygen attached to the surface layer of the iron powder may increase the oxygen content of the weld metal and reduce toughness, the upper limit of the content of iron powder may be limited to 8.0%, 6.0%, 4.0%, 2.0%, or 1.0%. Of course, iron powder is not essential in the flux-cored cut wire of the present invention, so the lower limit of the content of iron powder is 0%.

[0032] The impurities are components that are introduced into the flux-cored cut wire due to various factors in the manufacturing process or originate from the raw materials when the flux-cored cut wire is industrially manufactured. These are permissible within a range that does not adversely affect the flux-cored cut wire according to the present invention.

[0033] The flux-cored cut wire of the present invention may contain alloys, oxides, carbonates, etc. of other metal elements other than the high alloying elements, chemical components, strong deoxidizing elements, and impurity elements described above, within a range that does not impair the characteristics. In this case, the alloys, oxides, and carbonates of the other metal elements are not included in the contents of the high alloying elements, chemical components, strong deoxidizing elements, and impurity elements, as well as Fe and impurities. However, this does not mean that the alloys, oxides, and carbonates of these other metal elements are contained. That is, the flux-cored cut wire of the present invention has a chemical composition that contains the high alloying elements in a predetermined ratio, and the contents of the chemical components, strong deoxidizing elements, and impurity elements are each within a predetermined range, with the balance being Fe and impurities, or Fe, impurities, and alloys, oxides, and carbonates of these other metal elements. Preferably, the flux-cored cut wire has a chemical composition that contains the high alloying elements in a predetermined ratio, and the contents of the chemical components, strong deoxidizing elements, and impurity elements are each within a predetermined range, with the balance being Fe and impurities.

[0034] Furthermore, as long as the above-mentioned conditions are satisfied, the steel sheath of the flux-cored cut wire according to the present invention is not particularly limited. However, since the steel sheath is desirably made of mild steel, the chemical composition of the sheath may be, for example, in mass proportions, C: 0.1% or less, Si: 0.1% or less, Mn: 3.00% or less, P: 0.030% or less, S: 0.020% or less, Al: 0.1% or less, and N: 0.030% or less, with the remainder being iron and impurities.

[0035] The flux-cored cut wire of the present invention can be obtained by cutting a steel sheath filled with flux into wire-shaped pieces to a predetermined length. There is no particular restriction on the shape of the cut flux-cored cut wire, and a thin-diameter steel wire can be cut into pieces to a predetermined length to have a circular cross section, but considering that the flux is filled, the diameter is preferably φ1.0 to φ3.0 mm. Incidentally, the diameter of a conventional cut wire is about φ1.0 to φ2.0 mm. On the other hand, the length of the flux-cored cut wire is preferably 0.5 to 3.5 mm. The length of a typical cut wire is 0.5 to 2.0 times the wire diameter.

[0036] The flux filling rate is not particularly limited as long as the above-mentioned conditions are satisfied. For example, the lower limit of the flux filling rate, expressed as a mass ratio to the total mass of the flux-cored cut wire, may be 10% or 12%. The upper limit of the flux filling rate may be 80% or 90%.

[0037] Here, in order to reduce the amount of diffusible hydrogen in the weld metal, it is preferable that the amount of hydrogen contained in the flux-cored cut wire is 12 ppm or less relative to the total mass of the flux-cored cut wire. This amount of hydrogen intrudes during the manufacture of the flux-cored cut wire, and may also increase due to moisture intrusion during storage of the flux-cored cut wire. Therefore, if the period between the manufacture of the cut wire and its use is long, it is desirable to store the wire while preventing moisture intrusion.

[0038] The procedure for producing the flux-cored cut wire of the present invention is not particularly limited, but the following example can be given as a method for producing flux-filled wire before cutting. First, a method for producing a seamless flux-cored cut wire in which the seam of the steel sheath is welded and there are no slit-like gaps includes, in addition to a step of preparing flux so that the fluoride and chemical components are within a predetermined range, a step of forming a steel strip using a forming roll while feeding the steel strip in the longitudinal direction to obtain a U-shaped open tube, a step of supplying flux into the open tube through the opening of the open tube, a step of butt-welding the opposing edges of the opening of the open tube to obtain a seamless tube, a step of drawing the seamless tube to obtain a flux-cored wire having a predetermined wire diameter, and a step of annealing the flux-cored wire during or after the drawing step. The wire is then cut to a predetermined length to obtain a flux-cored cut wire.

[0039] Here, the butt welding is performed by electric resistance welding, laser welding, TIG welding, or the like. In addition, annealing is performed during the wire drawing process or after the wire drawing process is completed to remove moisture in the wire. Preferably, the annealing temperature is 650°C or higher and the annealing time is 4 hours or longer to make the H content in the wire 12 ppm or less. However, in order to prevent deterioration of the flux, the annealing temperature is 900°C or lower. Note that, instead of butt welding, a wire without slit-shaped gaps can be obtained by brazing the gaps in the steel sheath.

[0040] Also, the seam of the steel sheath may not be welded to obtain a flux-cored cut wire with a slit-shaped gap. In that case, the method is the same as the method for manufacturing a wire having a seamless shape, except that instead of the step of butt-welding the ends of an open pipe to obtain a seamless pipe, a step of forming an open pipe and butting the ends of the open pipe to obtain a pipe with a slit-shaped gap is included. The method for manufacturing a wire having a slit-shaped gap may further include a step of crimping the butted ends of the open pipe. In the method for manufacturing a wire having a slit-shaped gap, a pipe is drawn in a state in which a slit-shaped gap is present.

[0041] As described above, the flux-cored cut wire according to the present invention may be a wire cut from a seamless shape in which the seam of the steel sheath is welded and there is no slit-shaped gap, or a wire cut from a wire in which the seam of the steel sheath is not welded and there is a slit-shaped gap. However, it is preferable that the flux-cored cut wire is a wire cut from a steel sheath having no slit-shaped gap. H (hydrogen) that penetrates the welded part during welding diffuses into the weld metal and the welded material, accumulates in the stress concentration part, and causes cold cracking. There are various sources of H, but if the cleanliness of the welded part and the welding conditions are strictly controlled, the moisture (H2O) contained in the flux-cored cut wire can be a source of H, and the amount of this moisture may affect the amount of diffusible hydrogen in the welded joint. Therefore, a wire cut from a seamless shape in which there is no slit-shaped gap is preferable, but if the wire cut from a wire having a slit-shaped gap is cut, the flux-cored cut wire may be stored, for example, in a vacuum package or in a container that can maintain a dry state.

[0042] The flux-cored cut wire of the present invention may have an oil (lubricant) applied to its surface. The lubricant applied to the filler surface has the effect of suppressing rust generation during storage. Various types of lubricants (e.g., vegetable oils such as palm oil) can be used as such lubricants, but in order to suppress low-temperature cracking of the weld metal, it is preferable to use perfluoropolyether oil (PFPE oil) that does not contain H (hydrogen). When the flux-cored cut wire has a plating on its surface, the lubricant is applied to the plating surface.

[0043] [Method of manufacturing welded joints] Next, in manufacturing a welded joint using the above-mentioned flux-cored cut wire, the present invention includes a flux-cored cut wire welding process in which at least a part of a groove provided between base materials is filled with flux-cored cut wire and welded. That is, in manufacturing a welded joint, the flux-cored cut wire according to the present invention is filled in the groove of the base materials and welded in one or more of the first pass to the final pass. When welding is performed in only one pass, the flux-cored cut wire according to the present invention is used in that one pass.

[0044] An example of a flux-cored cut wire welding process according to the present invention is shown in Fig. 1 and Fig. 2. Fig. 1 shows an example in which a flux-cored cut wire 4 is filled in a part of a groove 3 provided between base materials 1 and 2, and welding is performed.

[0045] First, as shown in FIG. 1(a), a backing material 5 is attached to the back surface of the base materials 1 and 2, and then the flux-cored cut wire 4 according to the present invention is filled in the first layer in the groove 3. If strength and toughness are required only on the surface of the first layer, the flux-cored cut wire of the present invention may not be used in subsequent welding to produce a welded joint. If the deposition amount is insufficient with only the first layer, or if mechanical properties are required in the entire thickness, as shown in FIG. 1(c), the flux-cored cut wire 4 of the present invention is again dispersed on the weld metal 7 obtained including the flux-cored cut wire 4 filled in the first layer, and filled in the groove 3, and a welding wire 6 is placed to perform welding. This is then repeated, and when the required deposition amount is reached, welding can be performed without using the flux-cored cut wire of the present invention.

[0046] As shown in FIG. 2, the flux-cored cut wire welding process according to the present invention may be performed by flux-cored cut wire filling one-pass welding in which a flux-cored cut wire is filled in the groove and welding is performed in one pass. That is, as shown in Fig. 2(a), a backing material 5 is attached to the back surface of the base materials 1 and 2, and then the flux-cored cut wire 4 according to the present invention is dispersed so as to fill almost the entire groove 3, for example, about 80% of the height of the groove in the example of Fig. 2. Next, as shown in Fig. 2(b), a welding wire 6 is placed approximately on the center of the filled flux-cored cut wire 4, and an arc is generated to perform welding, thereby producing a welded joint by a weld metal 7 containing the flux-cored cut wire 4, as shown in Fig. 2(c).

[0047] In the example of the flux-cored cut wire welding process shown in FIG. 2, the flux-cored cut wire according to the present invention is used almost entirely within the groove, so that the strength and toughness of the weld can be ensured throughout the entire plate thickness.

[0048] 1 and 2 show an example in which the groove between the base materials is a so-called V-shaped groove, but the groove shape is not limited to this in the present invention, and other groove shapes such as I-shaped, L-shaped, K-shaped, J-shaped, X-shaped, U-shaped, H-shaped, and other groove shapes may be used. In addition, the present invention may be applicable to both single-sided welding and double-sided welding. Furthermore, in the case of multi-layer welding as in the example of FIG. 1, each layer may be welded in two or more passes.

[0049] The welding method (welding means) used in the present invention is not particularly limited, but in order to reliably melt the flux-cored cut wire filled in the groove, it is preferable to use submerged arc welding or gas-shielded arc welding. However, since it may be difficult to fill the groove with the flux-cored cut wire in vertical welding or overhead welding, the welding position is preferably downward or sideways.

[0050] Furthermore, the method for manufacturing a welded joint in the present invention is not particularly limited in terms of the type or shape of the base material, but is most effective when used in situations where low-temperature steel is used and construction efficiency is an issue.

[0051] (Example) Next, the present invention will be described in more detail with reference to examples. However, the following examples are not intended to limit the present invention, and any design modifications made within the spirit of the invention are within the technical scope of the present invention.

[0052] The flux-cored cut wires of the present invention and comparative examples (samples with wire numbers 1 to 35) were produced by the following method. First, a steel strip was fed in the longitudinal direction and formed using a forming roll to obtain a U-shaped open tube. Flux was supplied into the open tube through the opening, and the opposing edges of the opening of the open tube were butt-welded to obtain a seamless tube. This seamless tube was drawn to obtain a flux-cored wire without slit-shaped gaps. However, at this time, some samples were made into tubes with slit-shaped gaps without seam welding, and these were drawn to obtain wire. In this way, a flux-cored wire with a final filler diameter of φ2.0 mm was produced. During the wire drawing process, the flux-cored wires were annealed for 4 hours or more at a temperature range of 650 to 950°C. After the prototypes were made, a lubricant (PFPE oil) was applied to the surface of some of the wires. The manufactured flux-cored wires were then cut to a length of 2.0 mm to prepare samples of the flux-cored cut wires. In preparing the flux, for the highly alloying elements shown in Table 1, Ni, Cr, Mo, and W were used as their respective metal (alloy) powders, and for the chemical components shown in Table 2, C, Si, Mn, Cu, Nb, V, Al, B, and Bi were used as their respective metal powders, and for the strong deoxidizing elements shown in Table 2, Ca, Mg, and Ti were used as their respective metal (alloy) powders, and Zr and the elements Ce and La used as REM elements were used as their respective oxides. Note that the mass percentages of each element are shown in Table 1. The compositions of these flux-cored cut wires are shown in Tables 1 and 2.

[0053] [Table 1]

[0054] [Table 2]

[0055] The content of the high alloying elements (Ni, Cr, Mo, and W), optional chemical components, strong deoxidizing elements (Ca, Mg, Ti, Zr, and REM), iron powder (Fe powder), and each element contained as an impurity element listed in Tables 1 and 2 is expressed in units of mass percentage (mass%) relative to the total mass of the flux-cored cut wire.

[0056] The balance in the chemical composition of the flux-cored cut wire (i.e., components other than the elements disclosed in Tables 1 and 2) is iron (including intentionally added Fe powder) and impurities. The wire structure of each flux-cored cut wire is as shown in Table 1, and unless otherwise specified in the remarks column, no oil is applied. Meanwhile, each element contained in the flux-cored cut wire disclosed in Table 2 is contained in the steel sheath in the form of an alloy, or in the form of metal powder or oxide. In Tables 1 and 2, the blanks in the tables relating to the contents of the highly alloying elements, chemical components, strong deoxidizing elements, and Fe powder mean that the highly alloying elements, chemical components, strong deoxidizing elements, and Fe powder are not intentionally added. The highly alloying elements, chemical components, and strong deoxidizing elements may be unavoidably mixed in.

[0057] The flux-cored cut wires of the invention examples and comparative examples (samples with wire numbers 1 to 35) were evaluated by the method described below. A 9% Ni steel plate (JIS G 3127 SL9N steel plate) with a thickness of 20 mm was used, and SAW welding was performed in one pass under the welding conditions in Table 3. At that time, the groove shape was a V-shape as shown in Figure 3, and the thickness of the flux-cored cut wire 4 spread in the groove 3 was 18 mm. Furthermore, NITTETSU FLUX 10H manufactured by Nippon Steel & Sumitomo Metal Welding Co., Ltd. was used as the welding flux, and NITTETSU FILLER 196 (wire diameter φ4.8 mm) manufactured by Nippon Steel & Sumitomo Metal Welding Co., Ltd. was used as the welding wire. The welding wire was set perpendicular to the steel plate.

[0058] The mechanical properties of the weld metal of the welded joints produced by the above SAW welding were evaluated by the following procedure: Test pieces for tensile tests and test pieces for impact tests were taken from the welded joints produced by the above procedure, and were evaluated by tensile tests and impact tests in accordance with the JIS Z 3111:2005 test method. The tensile tests were performed on A2 test pieces according to JIS Z 3111:2005 taken from the weld metal (taken so that the longitudinal direction of the test piece coincided with the weld line direction), and the examples of test pieces having a tensile strength of 720 MPa or more were judged to be "passed" in terms of the mechanical properties of the weld metal. For the impact test, JIS Z 3111:2005 No. 4 test pieces (with the notch positioned in the center of the weld metal) were taken and subjected to impact testing at a test temperature of -196°C. Test pieces with an absorbed energy of 50 J or more were judged to have "passed" the low temperature toughness. As for the overall judgment, a specimen that passed both the tensile test and the impact test was judged to have "passed" in terms of mechanical properties.

[0059] [Table 3]

[0060] The test results evaluated by the above-mentioned methods are shown in Table 4. When welding was performed using the flux-cored cut wire of the invention, both strength and toughness were good, and all weld metals passed the test, meaning that weld metals with excellent mechanical properties could be produced. On the other hand, the comparative example was insufficient in either strength or toughness and was therefore rejected.

[0061] [Table 4]

[0062] As described above, according to the present invention, even if the base material is a steel for low temperature use, it is possible to produce a welded joint having excellent mechanical properties with high processing efficiency by SAW welding. [Explanation of symbols]

[0063] 1, 2: Base material (steel), 3: Groove, 4: Flux-cored cut wire, 5: Backing material, 6: Welding wire, 7: Weld metal.

Claims

1. A method for manufacturing a welded joint in which a cut wire is filled in a groove provided between base materials and welded by submerged arc welding, A welding method in which a flux-cored cut wire having a steel sheath and flux filled inside the steel sheath is filled into the groove, The flux contains one or more highly alloyed elements selected from the group consisting of Ni, Cr, Mo, and W as metals and / or alloys, and the total content of the highly alloyed elements is 50% or more and 98% or less in terms of mass ratio to the total mass of the flux-cored cut wire, A method for manufacturing a welded joint, characterized in that the Ni content is 50 mass% or more of the total content of the high alloying elements.

2. The flux-cored cut wire has a mass ratio relative to the total mass of the flux-cored cut wire of: The contents of the chemical components consisting of C, Si, Mn, Cu, Nb, V, Al, B, and Bi are C: 0.120% or less, Si: 2.00% or less, Mn: 3.50% or less, Cu: 5.00% or less, Nb: 0.50% or less, V: 0.500% or less, Al: 1.70% or less, B: 0.020% or less, and Bi: 0.030% or less, and the content of one or more strong deoxidizing elements selected from the group consisting of Ca, Mg, Ti, Zr, and REM is 4.0% or less in total, and 2. The method for manufacturing a welded joint according to claim 1, characterized in that the contents of the impurity elements P and S are P: 0.030% or less and S: 0.020% or less.

3. 3. The method for manufacturing a welded joint according to claim 2, characterized in that the strong deoxidizing element is contained in the flux-cored cut wire as an oxide and / or an alloy, and the total content thereof is 0.0005% or more and 4.0% or less in terms of mass ratio to the total mass of the flux-cored cut wire.

4. A cut wire for groove filling that fills a groove between base materials to manufacture a welded joint, A steel sheath and a flux filled inside the steel sheath, The flux contains one or more highly alloyed elements selected from the group consisting of Ni, Cr, Mo, and W as metals and / or alloys, and the total content of the highly alloyed elements is 50% or more and 98% or less in terms of mass ratio to the total mass of the flux-cored cut wire, A flux-cored cut wire for groove filling, characterized in that the Ni content is 50 mass% or more of the total content of the high alloying elements.

5. The flux-cored cut wire has a mass ratio relative to the total mass of the flux-cored cut wire of: The contents of the chemical components consisting of C, Si, Mn, Cu, Nb, V, Al, B, and Bi are C: 0.120% or less, Si: 2.00% or less, Mn: 3.50% or less, Cu: 5.00% or less, Nb: 0.50% or less, V: 0.500% or less, Al: 1.70% or less, B: 0.020% or less, and Bi: 0.030% or less, and the content of one or more strong deoxidizing elements selected from the group consisting of Ca, Mg, Ti, Zr, and REM is 4.0% or less in total, and 5. The flux-cored cutting wire for groove filling according to claim 4, characterized in that the contents of impurity elements P and S are P: 0.030% or less and S: 0.020% or less.

6. The flux-cored cut wire for groove filling according to claim 5, characterized in that the strong deoxidizing element is contained in the flux-cored cut wire as an oxide and / or an alloy, and the total content thereof is 0.0005% or more and 4.0% or less in mass ratio to the total mass of the flux-cored cut wire.

7. The flux-cored cut wire for groove filling according to any one of claims 4 to 6, characterized in that it is used by filling a groove provided between base materials.

Citation Information

Patent Citations

  • JP1974016023A

  • Oneeside arc welding method for 9* ni steel

    JP1978113734A

  • Starting method for electroslag welding

    JP1986216881A

  • Picture reader

    JP1989018365A

  • SINTERED TYPE FLUX FOR SUBMERGED-ARC WELDING FOR 9% Ni STEEL

    JP2011025285A